APPLYING INTERNATIONAL EXPERTISE IN FORMING DEPRECIATION POLICY FORMATION IN UKRAINE - Rak, R.; Mokhnach, T. (Visnyk Kyïvsʹkoho nat͡s︡ionalʹnoho universytetu imeni Tarasa Shevchenka. Ekonomika, 2022)
Depreciation policy is one of the main components of the state economic policy. The specifics of its implementation depend on the general state of the country’s economy development and the main tasks set for the nation or an individual enterprise. Depreciation policy is closely related to the tax system of the state, the procedure for accounting for non-current assets, and pricing. In contrast, depreciation deductions are an essential source of self-financing for enterprises. Therefore, the depreciation policy is subject to special attention from the state and each enterprise. However, in Ukraine, unlike most developed countries, the main directions of the depreciation policy of enterprises are not adequate. The article considers the development and operating patterns of depreciation policy of Ukrainian enterprises. Depreciation methods according to international and national standards have been studied. The ascertained components of the depreciation policy included the calculation of depreciation rates and amounts; distribution of accrued depreciation on separate analytical expense accounts; determination of the liquidation value of the object of fixed assets and other non-current assets, selection of the period of useful use of the object of fixed assets and other non-current assets, and others. The article studies the specifics of the depreciation policy of enterprises in Eastern Europe and G7 countries and, by comparing the depreciation policy of domestic enterprises and those in the countries under consideration, highlights appropriate ways to improve the depreciation policy for Ukrainian companies. The conclusion outlines proposals to improve the efficacy of domestic depreciation policy through applying international expertise and measures the potential impact of the proposed changes on the depreciation policy and economic efficiency of domestic enterprises.